Aromatic amine passivated TiO2 for dye-sensitized solar cells (DSSC) with similar to 9.8% efficiency - Kumar, T. R. Naveen; Yuvaraj, S.; Kavitha, P.; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Neppolian, B. (Solar Energy, 2020)
In this work, the efficiency of dye-sensitized solar cells (DSSC) was improved by capping TiO2 with simple aromatic amines as a complexing agent. The aromatic amines, aniline and o-phenylenediamine capped TiO2 composites were synthesized via hydrothermal route and used as scattering layer in dye-sensitized solar cell (DSSC). Markedly, the maximum photo-conversion efficiency of 9.84% was achieved with o-phenylenediamine capped-TiO2 composite as o-phenylenediamine capped-TiO2 showed higher reflectivity than the pristine TiO2, which is highly beneficial for reflecting the photons back to photoanode. In addition, the average life time of carriers in o-phenylenediamine capped-TiO2 was found to be 9.8 ms, which was 2 times higher than the pristine TiO2 (4.29 ms).
Keywords: Aromatic amines; DSSC; Electron injection; lifetime; Scattering layer; TiO2